2010
DOI: 10.1007/s11427-010-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cardiomyocyte differentiation from human embryonic stem cells

Abstract: Several approaches have been used to encourage the differentiation of cardiomyocytes from human embryonic stem cells. However, the differentiation efficiency is low, and appropriate culture protocols are needed to produce adequate numbers of cardiomyocytes for therapeutic cell transplantation. This study investigated the effects of serum on cardiomyocyte differentiation in suspension culture medium during embryoid body (EB) formation by human embryonic stem cells. The addition of ascorbic acid, dimethylsulfoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Evaluation of mesodermal markers like HAND1, MEF2C, GATA-4 and C-actin revealed a considerable upregulation of all these genes in low and medium dose, whereas highest dose of DMSO triggered significant downregulation of HAND1, GATA-4 and C-actin. These results indicate that DMSO at low and medium doses can act as an inducing agent for the formation of mesodermal phenotypes as also evidenced by the earlier reports (Wang et al 2010). Although DMSO is known to differentiate P19CL6 embryonic carcinoma cells into cardiomyocyte-like cells, the low differentiation capacity of DMSO reduces its usefulness (Seya et al 2011).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Evaluation of mesodermal markers like HAND1, MEF2C, GATA-4 and C-actin revealed a considerable upregulation of all these genes in low and medium dose, whereas highest dose of DMSO triggered significant downregulation of HAND1, GATA-4 and C-actin. These results indicate that DMSO at low and medium doses can act as an inducing agent for the formation of mesodermal phenotypes as also evidenced by the earlier reports (Wang et al 2010). Although DMSO is known to differentiate P19CL6 embryonic carcinoma cells into cardiomyocyte-like cells, the low differentiation capacity of DMSO reduces its usefulness (Seya et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…3c). Our results reassure the long-standing concept that DMSO at low and medium concentrations can act as an inducing agent for the formation of mesodermal phenotypes (Wang et al 2010).…”
Section: Quality Testing Of Hescsupporting
confidence: 86%
“…There are studies and reports demonstrating that many signaling pathways or compounds are involved in, such as STAT3, BMP, Wnt, FGF, PGC-1α, and reactive oxygen species. [25][26][27][28][29][30] It was not surprising that the state of the signaling pathways or compounds during differentiation might be modulated by a strong extracellular stimulus of 150 mg/L CRP, but not by a weaker stimulus of 30 mg/L CRP. Nevertheless, the present study demonstrated the effect of 150 mg/L CRP on the cardiac differentiation of ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…NaB has also been shown to promote the rapid differentiation of hESCs to primitive endoderm and trophectoderm lineages induced by nutlin, a small molecule activator of p53 (Maimets et al, 2008). Cardiomyocyte differentiation has been demonstrated to be enhanced by 5-azacytidine/5-aza-2′-deoxycytidine (Xu et al, 2002;Yoon et al, 2006;Wang et al, 2010), a chemical analogue of cytidine that acts as a false substrate for DNA methyltransferases, therefore reducing cellular DNA methylation content. A reduction in DNA methylation, similar to an increase in histone acetylation, induces the reactivation of genes associated with the differentiation of hESCs, and thereby primes them for appropriate signals to allow lineagespecific differentiation.…”
Section: Chromatin Landscape Modulation In Hesc Differentiationmentioning
confidence: 99%